On combining the Internet of Things with crowdsourcing in managing emergency situations - Lambrinos, Lambros (My University, 2015)
During emergency situations, collecting accurate information and in a timely manner is becoming more of the essence especially when lives are in danger. Crowdsourcing is an established method that relies on people to provide information on their surroundings or ongoing incidents something which in many cases is achieved through mobile applications. The Internet of Things on the other hand, relies on sensors and Machine-to-Machine (M2M) communications to acquire data which is then analysed centrally. Combining the two in a common platform is the subject of this paper: we aim to collectively utilize the accuracy of the data gathered by the Internet of Things with the more contextual information provided by people in order to enhance existing mechanisms for detecting and subsequently managing emergency situations.
Keywords: Crowdsourcing; Emergency situation; Internet of Things; Mobile application; Sensor networks